Computational evaluation of the impact of incorporated nitrogen and oxygen heteroatoms on the affinity of polyaromatic ligands for carbon dioxide and methane in metal–organic frameworks - Henley, Alice; Lennox, Matthew J.; Easun, Timothy L.; Moreau, Florian; Schröder, Martin; Besley, Elena (American Chemical Society, 2016)
Density functional theory is employed to explore the binding of carbon dioxide and methane in a series of isoreticular metal–organic frameworks, with particular emphasis on understanding the impact of directly incorporated nitrogen and oxygen heteroatoms on the affinity of the ligand for CO2 and CH4. While the strongest binding sites for both CO2 and CH4 were found to be directly above the aromatic rings of the core of the ligand, the introduction of heteroatoms to the core systems was shown to significantly alter both the binding strength and preferred binding locations of CH4 and CO2. The presence of pyrazine rings within the ligand was observed to create new binding sites for both CO2 and CH4 and, in the case of CO2, severely reduce the binding strength or entirely eliminate binding sites that were prominent in the analogous carbocyclic ligands. These results suggest that while the presence of framework nitrogen and oxygen heteroatoms provides a route to ligands with enhanced affinity for methane, a similar increase in affinity for CO2 is not guaranteed.